Sangeetha Pulapaka
0

STEP 1: Recall what is a polynomial

https://www.mathsisfun.com/algebra/polynomials.html

STEP 2: Recall division between two polynomials

https://www.qalaxia.com/viewDiscussion?messageId=5d1e18c64c79a4745265f5a3

STEP 3: Recall the remainder theorem

https://www.khanacademy.org/math/algebra2/arithmetic-with-polynomials/polynomial-remainder-theorem/v/polynomial-remainder-theorem

STEP 4: The remainder Theorem states: 

When you divide a polynomial f(x) by x - c the remainder r will be f(c)


In this case f(x) =   2x^{2} - 5x + 6 and c = 2

Therefore r = f(2) = 2 × 22 - 5 × 2 + 6 = 8 - 10 + 6 = 4